Alcohol age of initiation and long-term impact: a cross sectional survey of adults in England. (3rd March 2016) - Morleo, Michela; Jones, Lisa; Bellis, Mark A.
Abstract: Background : Worldwide alcohol consumption is involved in 2.5 million deaths annually. Worryingly, the age of alcohol initiation may be decreasing; evidence suggests an inverse correlation between initiation and prevalence of alcohol use. European data are limited. Methods : Data are from a survey ( n = 2638) on alcohol consumption of ≥18 y in England. Univariate and multivariate associations are reported between demography, last year alcohol consumption, historic drinking including having regularly drank alcohol <18 y (drank at least monthly), and experience of at least one serious alcohol-related problem (self-defined). Results : Lifetime alcohol consumption was reported by 93.2% of participants. Of these, 36.1% reported regular consumption <18 y; 18–30 y had a threefold greater odds of reporting alcohol consumption <18 y than 61–75 y. In total, 5.2% reported at least one serious alcohol-related problem; those who had regularly consumed alcohol <18 y had a twofold greater odds of reporting this than those who had not. Conclusion : Our sample supports a potential increase in the proportion of those reporting underage alcohol initiation. As those who regularly consumed alcohol <18 y were at risk of experiencing alcohol-related problems, incidence of harm could increase over time as early initiators start to experience harms, supporting the need for interventions to delay alcohol consumption in underage groups.